Numerical Prediction of Failure within Small Curvature Bending of Advanced High Strength Steels - Tsoupis, Ioannis; Merklein, Marion (Key Engineering Materials, 2015)
Within this paper a numerical study of the Continuum Damage Mechanics based damage model Lemaitre in commercial software LS-DYNA is performed in order to correctly predict failure in terms of crack occurrence within small curvature bending of AHSS steels. A strain based calibration method is used for the effective adaption of the Lemaitre model to the bending operation, which is based on the comparison and adaption of the numerically calculated and the experimentally measured deformation field on the outer surface of the bent specimen. Within this method the material dependent damage parameter S is systematically varied in the simulation in order to represent maximum major strain. The new method is proved by numerical simulation of experiments provoking crack initiation using smaller bending radii. It can be shown that failure in terms of crack initiation can be correctly predicted by the model with the damage parameters, which were determined by the method of strain based calibration and an additional optimisation of the parameter Dc. Thus, within this study a user friendly and effective way for the application of Lemaitre damage model to small curvature bending processes of AHSS steels is developed.
LFT Import::2019-07-29 (2076)
Keywords: Bending; Damage; Simulation